2018
DOI: 10.1002/mma.5196
|View full text |Cite
|
Sign up to set email alerts
|

Two different fractional Stefan problems that are convergent to the same classical Stefan problem

Abstract: Two fractional Stefan problems are considered by using Riemann-Liouville and Caputo derivatives of order ∈ (0, 1) such that, in the limit case ( = 1), both problems coincide with the same classical Stefan problem. For the one and the other problem, explicit solutions in terms of the Wright functions are presented.We prove that these solutions are different even though they converge, when ↗ 1, to the same classical solution. This result also shows that some limits are not commutative when fractional derivatives… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It is worth noting that this kind of problems are not deduced as in [17,27]. This paper is a continuation of a previous work [20], related to fractional one-phase change problems. In Section 2 some basic definitions and properties on fractional calculus are given.…”
Section: This Paper Deals With Stefan-like Problems Governed By Fract...mentioning
confidence: 88%
See 1 more Smart Citation
“…It is worth noting that this kind of problems are not deduced as in [17,27]. This paper is a continuation of a previous work [20], related to fractional one-phase change problems. In Section 2 some basic definitions and properties on fractional calculus are given.…”
Section: This Paper Deals With Stefan-like Problems Governed By Fract...mentioning
confidence: 88%
“…From [23] we know that f 1 is a strictely decreassing function in R + . Taking a close interval [a, b] ⊂ R + such that η 1 ∈ [a, b], using the uniform convergence over compact sets of all the positive functions given in Proposition 6 and proceding like in [20,Theorem 2] we can state that lim α 1 η α = η 1 .…”
Section: Theorem 1 [19]mentioning
confidence: 99%
“…This result encouraged the researchers to investigate the time-fractional Stefan model more deeply. In papers, [6][7][8][9][10] the authors discussed other possible formulations of time-fractional Stefan problem and compare the formulas for special solutions. In paper, 11 there is shown that the time-fractional sharp-interphase model obtained in Falcini et al 1 is not a consequence of the assumption (1).…”
Section: Introductionmentioning
confidence: 99%
“…Different models are presented in [7], [18] and [26]. A rigorous existence analysis of self-similar solutions was done in [9], and results related to explicit solutions were established in [17,20,19] and references therein.…”
Section: Introductionmentioning
confidence: 99%